The formation of the school of Arabic Studies in Germany - Kholdarov Akmaljan (Genius Journals, 2023)
To study the achievements of Muslim science in the 11th-13th centuries. mainly Spanish or Italian scientists set themselves the task. By the 17th-19th centuries, German scientists began to play an important role in these studies. During this period, scientific studies of the “Muslim civilization” and Arabic linguistics significantly expanded in German historiography. The translation of Arabic works on Eastern philosophy into German has accelerated. Arab linguists, orientalists, Arabists appeared. Thanks to this, the practical application of the achievements of Muslim science in the life of European peoples in the "advanced era" caused many positive developments
Keywords: Arabia; Germany; Erich Brionli; Arabic studies